Primary tumor resection benefited the survival of patients with distant metastatic gastric cancer - Gao, Yan (J Res Med Sci, 2021)
BACKGROUND: The role of surgery in the treatment of patients with distant metastatic (M1) gastric cancer (GC) remains controversial currently. This study aimed to clarify the impact of primary tumor resection (PTR) on the survival of such patients. MATERIALS AND METHODS: The surveillance, epidemiology, and end results database was adopted to extract eligible patients. We designed a retrospective case–control study. The patients were divided into two groups according to whether they received PTR. The 1:1 propensity score matching (PSM) analysis was performed to balance the confounding factors between no-surgery and surgery groups. The categorical variables were described with Chi-square tests. Cancer-specific survival (CSS) and overall survival (OS) were evaluated by Kaplan–Meier method with log-rank test. Cox proportional hazard models were utilized to identify prognostic factors of CSS. RESULTS: A total of 1716 patients were included, including 1108 (64.6%) patients without surgery and 608 (35.4%) patients with surgery. After PSM, most confounders were well balanced between the two comparison groups. Survival analysis in matched cohorts indicated that surgery exerted significant survival advantages in both CSS and OS curves. The median CSS was 11.0 (9.8–12.2) months in the surgery group versus 9.0 (8.0–10.0) months in the no-surgery group (P < 0.001). Multivariable Cox regression analysis identified surgery as an independent prognostic factor for favorable prognosis (hazard ratio: 0.689, 95% confidence interval: 0.538–0.881, P = 0.003). CONCLUSION: Surgery showed significant survival benefits for the patients with M1 stage GC. Our study has provided additional evidence to support PTR for these patients.